Collins COBUILD phrasal verbs dictionary 2026-02-15T18:24:54+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Gautier, Phyllis; Macaulay, Alison; Seaton, Maggie (Collins COBUILD, 2011)

(untitled)
This reissue of the second edition of the Collins COBUILD Dictionary of Phrasal Verbs offers comprehensive coverage of the most important phrasal verbs in English